Left Dislocation in Indonesian - Heejin Jung (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2021)
This paper aims to identify the constructions of Left Dislocation (=LD) in spoken and written Indonesian. The constituents of LD fill their alternative positions within the core clause with the form of ‘-nya’ in Indonesian syntax. The Left Dislocation of ‘-nya’ is classified as the Clitic-type Left Dislocation. A coreferential copy of '-nya' is presented grammatically without variation, and this clitic presents a metonymic link between the referents of LD constructions. This study found that there is strong connectivity in Indonesian between the dislocated constituent and the core clause. LD in Indonesian allows a higher degree of Topic-prominence than other languages which were classified typologically as Subject-prominent languages. In the light of this Topic-prominence in Indonesian in the LD structures, this paper revises the relation between Topicalization and LD. The phenomenon of Topicalization is proposed to be merged within the notion of LD and be explained as Zero-type LD. It is concluded that the LD structures in Indonesian represent Topic-prominence features to classify Indonesian as the language that is both Subject-prominent and Topic-prominent.